Sustainability in the global city : myth and practice - Isenhour, Cindy; McDonogh, Gary W.; Checker, Melissa (Cambridge : Cambridge University Press, 2015)
Cities play a pivotal but paradoxical role in the future of our planet. As world leaders and citizens grapple with the consequences of growth, pollution, climate change, and waste, urban sustainability has become a ubiquitous catchphrase and a beacon of hope. Yet, we know little about how the concept is implemented in daily life - particularly with regard to questions of social justice and equity. This volume provides a unique and vital contribution to ongoing conversations about urban sustainability by looking beyond the promises, propaganda, and policies associated with the concept in order to explore both its mythic meanings and the practical implications in a variety of everyday contexts. The authors present ethnographic studies from cities in eleven countries and six continents. Each chapter highlights the universalized assumptions underlying interpretations of sustainability while elucidating the diverse and contradictory ways in which people understand, incorporate, advocate for, and reject sustainability in the course of their daily lives.
Introduction Melissa Checker, Gary McDonogh and Cindy Isenhour; Part I. Building the Myth: Branding the Green Global City: 1.'We're not that kind of developing country': environmental awareness in contemporary China Jennifer Hubbert; 2. Green capitals reconsidered Cindy Isenhour; Snapshot 1. Transparency, consumerism, and governmentality: lessons from a very small place Gary McDonogh; 3. Going green?: washing stones in world-class Delhi Varsha Patel; Part II. Planning, Design, and Sustainability in the Wake of Crisis: 4.'The sustainability edge': the postcrisis promise of eco-city branding Miriam Greenberg; Snapshot 2. Developing sustainable visions for post-catastrophe communities Daniel Slone; 5.'I've got a house but no room for my hammock': the tragedy of the commons; or, another common tragedy among the Aiu of Sinamaica, Venezuela Ana Servigna and Ali; Fernandez; 6. Green is the new brown:'old school toxics' and environmental gentrification on a New York City waterfront Melissa Checker; Snapshot 3. Producing sustainable futures in post-genocide Kigali, Rwanda Samuel Shearer; Part III. Everyday Engagements with Urbanity and'Nature': 7. Whose urban forest?: The political ecology of gathering urban nontimber forest products Patrick Hurley, Marla R. Emery, Rebecca McLain, Melissa Poe, Brian Grabbatin and Cari Goetcheus; Snapshot 4. One man's trash Brad Rogers; 8. Shopping on Main Street: a model of a community-based food economy Kathleen Bubinas; 9. Spokespeople for a mute nature: the case of the Villa Rodrigo Bueno in Buenos Aires Mari;a Carman; Part IV. Cities Divided: Urban Intensification, Neoliberalism, and Urban Activism: 10. Combining sustainability and social justice in the Paris metropolitan region Francois Mancebo; 11. Shifting gears: the intersections of race and sustainability in Memphis Matthew Farr, Keri Brondo and Scout Anglin; 12. Can human infrastructure combat green gentrification?: Ethnographic research on bicycling in Los Angeles and Seattle Adonia Lugo; 13. Urban sustainability as a'boundary object': interrogating discourses of urban intensification in Ottawa Donald Leffers; 14. Learning'just' sustainability: a collaboration between the Preserve East Austin Affordability Campaign and the frontiers of geography class Eliot Tretter; Snapshot 5. After sustainability: Barcelona in a time of crisis Gary McDonogh; Afterword Alf Hornborg.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Sustainable urban development; Urban anthropology; Urban ecology (Sociology); Urbanization -- Social aspects